Increasing Students’ Vocabulary Mastery Using English Subtitle In Movie At SMA Negeri 9 Binsus Manado. - Rumambi, Lea; Rombepajung, Paula; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Vocabulary is one of several important things to know in learning a language. Having rich vocabulary knowledge is a key element to better reading comprehension The purpose of this research is to find out whether using English subtitle in the movie can increase Students’ vocabulary or not. There are 33 eleventh grade students at SMA Negeri 9 Binsus Manado participate in this research. This research used pre-experimental design with one group pre-test and post-test. Pre-test was given before treatment and post-test given after the treatment. The movie used in this research entitled “The Chronicles of Narnia: The Lion, the Witch and the Wardrobe” released in 2005. Matching words test consist of 20 number is the test used in pre-test and post-test for students. The result mean score of pre-test is 75 and the mean score of post-test is 97.42. The results showing higher score after treatment was given to students. It can be concluded that using English subtitle in the movie can increase Students’ vocabulary